Horizontal Gated Communities and the Segregation of Urban Space: Impact Assessment and Intervention Proposals - Kowalski, Luiz Fernando; Olivatto, Tatiane Ferreira; Bon, Frederico Pedro; Masiero, Erico; Fernandes, Ricardo Augusto Souza (National Journal of City Management, 2021)
Horizontal gated communities (HCGs) affect the dynamics of cities, as they are obstacles to mobility, integration and democratic use of public space. In this work, we investigate the negative impacts caused by these ventures and propose mitigation measures from the perspective of urban planning. This was based on bibliographic materials and a collection of interventions found in the literature, which led to a proposal of intervention on the walls of an HCG located in the Brazilian city of Engenheiro Coelho/SP. The focus of the proposed intervention was the outsourcing of part of the public green areas, visual permeability and improvement of access. The intervention proposals aimed at urban democratization and the resilience of communities impacted by this type of real estate development, in addition to restoring the right to enjoy the city and minimizing socio-spatial segregation, ensuring access to public areas and greater compliance with urban mobility policies.